2008
DOI: 10.12968/ijtr.2008.15.1.27946
|View full text |Cite
|
Sign up to set email alerts
|

Measuring occupational performance and client priorities in the community: The COPM

Abstract: The primary aim of this study was to examine changes in clients' occupational performance and satisfaction with their performance within a community trust setting, using the Canadian Occupational Performance Measure (COPM). Given the rapid throughput of clients and the pressure of limited resources, the authors postulated that occupational therapy interventions were focusing on clients' self-care needs as a matter of priority for clients to be independent at home. Therefore, at a time when services are seeking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…This is similar to what was found in a study of women with a Colles fracture (4). Other studies that included mixed groups regarding gender and diagnoses found quite different distributions (32,37,38). Our findings may therefore indicate a characteristic pattern of performance problems in elderly women with fractures of the antebrachium.…”
Section: Occupational Performancesupporting
confidence: 90%
“…This is similar to what was found in a study of women with a Colles fracture (4). Other studies that included mixed groups regarding gender and diagnoses found quite different distributions (32,37,38). Our findings may therefore indicate a characteristic pattern of performance problems in elderly women with fractures of the antebrachium.…”
Section: Occupational Performancesupporting
confidence: 90%
“…Occupational Therapy International differences in the distribution of OPIs with variations related to the different settings, conditions, and ages [25,37,38]. The clients identified most of the OPIs in self-care (n = 200, 40%), as seen in other studies [36,37].…”
mentioning
confidence: 70%
“…Occupational Therapy International differences in the distribution of OPIs with variations related to the different settings, conditions, and ages [25,37,38]. The clients identified most of the OPIs in self-care (n = 200, 40%), as seen in other studies [36,37]. Because the COPM is known to help clients express what they really find distressing in their present lives, this finding makes sense, as many adults may express frustration and maybe humiliation with not being able to perform the self-care activities that they learned in childhood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The COPM has been used to measure the effectiveness of rehabilitation in neurological populations (Dawson et al, 2013;Nilsen et al, 2012;Page et al, 2013;Polatajko et al, 2012;Roberts et al, 2008;Taylor et al, 2012). One of the difficulties with using the COPM in neurological rehabilitation is the presence of aphasia (Chan and Lee, 1997;Chen et al, 2002;Dawson et al, 2013;Gilbertson and Langhorne, 2000;Parker and Sykes, 2006;Taylor et al, 2012;Wressle et al, 2002).…”
Section: Statement Of Contextmentioning
confidence: 99%